Hubungan status gizi dengan kejadian anemia pada remaja putri - Irma Miftahul; Suri Salmiyati; Suratini Suratini (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Anemia is a common health problem among adolescent girls, often triggered by poor nutritional status. Adolescent girls are susceptible to anemia due to iron deficiency and an unbalanced diet. This study aims to determine the relationship between nutritional status and the incidence of anemia in adolescent girls. Purpose: To determine the relationship between nutritional status and the incidence of anemia in adolescent girls. Metode: This study is a correlational descriptive quantitative study with a cross-sectional approach. The sampling technique used total sampling, involving 41 respondents. Data analysis was performed using the Spearman's rank correlation test. Results: A study of 41 respondents showed that 34.1% had normal nutritional status, 48.8% were underweight, and 17.1% were overweight. Regarding anemia, 36,6% of respondents were not anemic, 46.3% had mild anemia, and 17.1% had moderate anemia. The Spearman Rank statistical test showed a p-value of 0.037<0.05) proving a significant relationship between nutritional status and the incidence of anemia. Conclusion: There is a significant relationship between nutritional status and the incidence of anemia in adolescent girls, where poor nutritional status increases the incidence of anemia.   Keywords: Adolescent Girls; Anemia; Nutritional Status.   Pendahuluan: Anemia adalah masalah kesehatan yang umum terjadi pada remaja perempuan, yang seringkali dipicu oleh status gizi yang buruk. Remaja putri rentan mengalami anemia karena kekurangan zat besi dan pola makan yang tidak seimbang. Penelitian ini bertujuan untuk mengetahui hubungan antara status gizi dengan kejadian anemia pada remaja putri. Tujuan: Untuk mengetahui hubungan antara status gizi dengan kejadian anemia pada remaja putri. Metode: Penelitian ini merupakan penelitian kuantitatif deskriptif korelasional dengan pendekatan cross sectional. Teknik pengambilan sampel menggunakan total sampling, dengan melibatkan 41 responden. Analisis data dilakukan dengan menggunakan uji Rank Spearman. Hasil: Penelitian terhadap 41 responden menunjukkan bahwa 34.1% memiliki status gizi normal, 48.8% memiliki berat badan kurang, dan 17.1% memiliki berat badan berlebih. Mengenai anemia, 36.6% responden tidak mengalami anemia, 46.3% mengalami anemia ringan, dan 17.1% mengalami anemia sedang. Uji statistik Rank Spearman menunjukkan nilai p-value sebesar 0.037<0.05 yang membuktikan adanya hubungan yang signifikan antara status gizi dan kejadian anemia. Simpulan: Terdapat hubungan yang signifikan antara status gizi dengan kejadian anemia pada remaja putri, dimana status gizi yang buruk meningkatkan kejadian anemia.   Kata Kunci: Anemia; Remaja Putri; Status Gizi.